Software educativo para la asignatura de matemática para los estudiantes del séptimo año de educación general básica de la escuela “Dr. Edison Calle Loaiza” de la provincia de Loja, periodo 2014 - 2015 - Jara Armijos., Diana Elizabeth (2015)
This thesis refers to: EDUCATIONAL SOFTWARE FOR MATH COURSE FOR STUDENTS OF THE SEVENTH YEAR OF BASIC GENERAL EDUCATION SCHOOL "DR. EDISON CALLE LOAIZA" OF THE PROVINCE OF LOJA, PERIOD 2014 -2015, the same that was developed according to Regulation of Academic System of the National University of Loja. It poses as central problem: to analyze the development educational software for mathematics program for students in the seventh year of basic general education school "Dr. Loaiza Edison Street "in the Province of Loja The overall objective: develop an educational software for mathematic courses for students of the seventh year of basic general education school "Dr. Edison Calle Loaiza" in the Province of Loja. The methods used for the preparation of this research were: Scientific, deductive, inductive, Statistical Model, the same that served effectively help to achieve the proposed goal. Among the techniques and instruments used were: Observation Form applied to students in the seventh year for classroom activities, Interview applied to teachers to determine the resources required for software development, survey applied to the students to determine the educational software requirements. According to the results it is concluded that: 91% of students say they would like to learn through educational software the mathematics, 97% of students believe that significantly improve the knowledge acquired in mathematics and This academic performance, thus significantly help educational software as a teaching resource to support classroom activities and improve the teaching and learning process. According to the results of the survey of the teaching of the subject of mathematics, it is concluded that: the teacher agrees that the educational software improve student learning, in addition to the teacher-student interaction.